Development of Virtual Tour Media of Sambisari Temple as a History Learning Media in High Schools - Nurbaiti Islami Chotimah, Anisa; Sariyatun, Sariyatun; Ardianto, Deny Tri (JTP - Jurnal Teknologi Pendidikan, 2024)
This study aims to develop a Virtual-based learning media centered on Sambisari Temple  to enhance the quality of history education. The research employed the Research and Development (R&D) method using the ADDIE model. Data were collected through interviews, observations, and questionnaires involving 30 tenth-grade students at SMA Angkasa Adisucipto. The data analysis revealed that the Virtual Tour Sambisari Temple  application, developed using tools like Blender, Unity 2022, and Canva, demonstrated high feasibility. The material validation received an average score of 93%, and media validation achieved 79%, both categorized as “feasible”. The trial with students showed an average response score of 81.76% classified as “very practical”. The application features interactives tools, 260-degree visual panoramas, and historical information aligned with the curriculum, presented in an engaging format. It operates both online and offline, allowing students to explore historical sites effectively without visiting the location in person. The findings indicate that the Virtual Tour Sambisari Temple  application enhances students’ understanding of history topics and motivates them to learm through innovative and engaging approaches. This study provides a framework for integrating technology inti learning media, paving the way for future developments in educational technology.